Indicators for sustainable development of agriculture. Theoretical premises and proposed measurement in regions of the EU - Matuszczak, Anna (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
The article pointed out the desirability of considering sustainable development of agricultural at regional level. Against the backdrop of the agrarian economy assumptions, presents an approach to the concept of sustainable development, referring to the relationship between the orders of cohesion (economic, social and environmental), sustainable development and integrated order. Overview formed the theoretical basis for the operationalization of the measurement of sustainable development of agriculture in the EU regions. Based on FADN data for the average farm in the EU region (or the type of production or economic power) proposes to construct a synthetic indicator of the development of agriculture of these regions using the Hellwig’s method. Then the linear ordering allows the isolation of European regions, where agriculture will be considered: sustainable, medium or high unsustainable.
Keywords: sustainable development; agriculture; indicators